2017
DOI: 10.1515/humo-2017-0040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tactical principles efficiency among soccer players from different game positions

Abstract: Purpose. the aim of the study was to analyse the execution efficiency of core tactical principles in young soccer players and compare them among different game positions. Methods. the sample included 54 Brazilian young soccer players. tactical performance was measured by the System of tactical Assessment in Soccer with the Gr3-3Gr test in 3770 tactical actions. Friedman followed by Wilcoxon tests were used to analyse differences between tactical principles. Kruskal-Wallis and Mann-Whitney U tests were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…On the other hand, considering the offensive tactical principles, we found no differences between different positional roles. This result is in contrast with earlier findings from Padilha et al (2013) and Rechenchosky et al (2017), which studies found the differences among positional roles in offensive unity. This tactical principle is related to team's cohesion and balance between the longitudinal and transversal lines in the offensive actions, and the mentioned studies found that midfielders outperformed defenders and forwards in such actions.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, considering the offensive tactical principles, we found no differences between different positional roles. This result is in contrast with earlier findings from Padilha et al (2013) and Rechenchosky et al (2017), which studies found the differences among positional roles in offensive unity. This tactical principle is related to team's cohesion and balance between the longitudinal and transversal lines in the offensive actions, and the mentioned studies found that midfielders outperformed defenders and forwards in such actions.…”
Section: Discussioncontrasting
confidence: 99%
“…We would like to acknowledge that the TacticUP video test for soccer used the same theoretical background of the FUT-SAT (Teoldo et al, 2011b), which scientific knowledge has been produced since 2009. Among the studies carried out with FUT-SAT, there are empirical data that support the important role and relationship of tactical skills with: (i) sport development according to age (Teoldo et al, 2010;Américo et al, 2016;Borges P. H. R. et al, 2017); (ii) relative age effects, which are (dis)advantages between players born in different quartiles within a sport season (Teoldo et al, 2010b;; (iii) players' positional role Rechenchosky et al, 2017a); (iv) training intervention programs (Souza et al, 2014;Aquino et al, 2015); (v) affective decision-making (Gonzaga et al, 2014;Andrade et al, 2016);(vi) training constraints (e.g., numerical superiority) (Bredt et al, 2016;Padilha et al, 2017); (vii) motor and technical skills (Praça et al, 2015;Aquino et al, 2016); (viii) peripheral perception (Gonçalves et al, 2017); (ix) maturation Gonçalves et al, 2017); and (x) mental fatigue (Kunrath et al, 2018). Therefore, both TacticUP video test and FUT-SAT measure complementary constructs of tactical concept (i.e., perceptual-cognitive skills and perceptual-motor skills) based on the same theoretical and pedagogical foundations (i.e., the core tactical principles).…”
Section: Discussionmentioning
confidence: 99%
“…In the last five years, some studies have used FUT-SAT with the purpose of understanding the DM in players of different ages. For example, Rechenchosky et al (2017) analyzed the effectiveness of tactical principles in an U15 group, comparing them among the different game positions (defender, midfielder and striker). Correia et al (2019) compared the quantity, quality and result of tactical actions in the U15 age group among professional and amateur soccer teams.…”
Section: Introductionmentioning
confidence: 99%